2018
DOI: 10.3389/fncel.2018.00242
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of in vitro Methods to Study Microglia

Abstract: Neuroinflammation is a common feature in neurodegenerative diseases and strategies to modulate neuroinflammatory processes are increasingly considered as therapeutic options. In such strategies, glia cells rather than neurons represent the cellular targets. Microglia, the resident macrophages of the central nervous system, are principal players in neuroinflammation and detailed cellular biological knowledge of this particular cell type is therefore of pivotal importance. The last decade has shed new light on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(157 citation statements)
references
References 137 publications
4
151
1
1
Order By: Relevance
“…In this regard, many authors in the last few years have reported that there are several substances of natural origin, as well as of a synthetic nature with the ability of inhibiting, both in vitro and in vivo, the PI3K/Akt inflammatory signaling pathway and, consequently, reducing the microglia activation and the inflammatory responses associated with this pathway. A number of in vitro models, including microglia cell lines, stem cell derived microglia cultures, and primary dissociated cell cultures, were performed in order to study the role of microglia in neurodegenerative disorders and, in particular, relevant to PI3K signaling (for more detail, see [73]). This anti-inflammatory beneficial effect could be linked to the ability of inhibiting PI3K/Akt signaling pathways [74,75].…”
Section: Pi3k Role In Neuroinflammationmentioning
confidence: 99%
“…In this regard, many authors in the last few years have reported that there are several substances of natural origin, as well as of a synthetic nature with the ability of inhibiting, both in vitro and in vivo, the PI3K/Akt inflammatory signaling pathway and, consequently, reducing the microglia activation and the inflammatory responses associated with this pathway. A number of in vitro models, including microglia cell lines, stem cell derived microglia cultures, and primary dissociated cell cultures, were performed in order to study the role of microglia in neurodegenerative disorders and, in particular, relevant to PI3K signaling (for more detail, see [73]). This anti-inflammatory beneficial effect could be linked to the ability of inhibiting PI3K/Akt signaling pathways [74,75].…”
Section: Pi3k Role In Neuroinflammationmentioning
confidence: 99%
“…Laboratory experimentation may generate different activation profiles from those found in live human brain tissue following a stroke, as in vitro cultures commonly demonstrate amoeboid morphologies and are generally considered to exhibit signs of low-level inflammatory activation [169]. Therefore, it may be more scientifically sound to caution against attempts to classify microglial populations as exhibiting a distinct phenotype and instead view microglial "activation" as specific to individual cells [60].…”
Section: Challenges For Stroke Therapies Targeting Microgliamentioning
confidence: 99%
“…The next challenge was to examine APC activity in different cell types, and to determine whether APC is secreted into the medium or attached to the cells. Two cells types were used; N9 cells as a model for microglia, and C6 cells as a model for astrocytes [24,25]. In order to distinguish between medium and cells derived activity, the serum-free medium was transferred into empty wells 24 h after initiating the experiment.…”
Section: Cell Culturesmentioning
confidence: 99%